MEDIA ROLE IN REPORTING COVID-19 PANDEMIC IN NIGERIA - Ibe, Nkechinyere Magdalene Awo; Asogwa, Fidelis Ndidiamaka; Orji-Egwu, Agatha Obiageri (The Melting Pot, 2021)
Globally, mass media play a very significant role in human life. This is because the media are all around us from the show on television such as music, movies and news, to jingles on the radio, and news reports on newspapers. These media offerings engender mutual understanding, socialisation, knowledge, entertainment, and surveillance if presented in a fair, unbiased and non-inflammatory manner. It is widely accepted that what we know about, think, and believe, outside of personal first-hand experience, is shaped by how these events are reported in the frontline medium especially during an outbreak of strange disease (s) where fear and panic thrive. It is against this backdrop that this study explores media role in reporting COVID-19 pandemic in Nigeria. The study adopts the Social Responsibility theory. It also adopts the qualitative methodology and relies on secondary data generated from relevant headlines from newspapers, television, and radio. The study found that the media, through their reports, are powerful agents in controlling the infection rate and control of the disease. The media also had the potential to unite the people who survived the disease and end their stigmatisation by constantly informing, creating awareness, and educating the general public on the government activities and safety protocols. The study recommends that the media should be integrated into medical emergency management protocol by health authorities in Nigeria, specialised training for journalists on Covid-19 mitigation measures, and institutional support for the media to continue to play its societal roles effectively.